THE ANALYSIS OF FACTORS AFFECTING THE INTENTION TO USE MOBILE PAYMENT IN THE POLYTECHNIC STUDENT OF BATAM - Suci Hanizal (Pusat P2M Politeknik Negeri Batam, 2023)
This study aims to examine the influence of cost perspective, financial risk perspective, security perspective, convenience perspective, age and gender on the use mobile payment in Polytechnic students. The object of this study is active students of Batam State Polytechnic specifically majoring in Business Management, Accounting and Managerial Accounting Study class of 2018. The total respondents were 95 students. The sampling technique in this study used the purposive sampling method by accounting and managerial accounting students for the Batam State Polytechnic employee class who had used QRcode. In addition, this study uses a quantitative methods and data collection through surveys by distributing questionnaires through google form. The result of this study is a perceived ease of use merely has a significant positive effect on the intention to use, while perceived financial risk, perceived security, age, and gender have no effect on the use of mobile payment.